Performance of IPEN-CNEN/SP neutron activation analysis laboratory for microelement determinations in proficiency testing. - ARMELIN, M. J. A. (2009)
The performance of Neutron Activation Laboratory, IPEN ? CNEN/SP, was evaluated for the Ca, Fe, K, Mn, Na and Zn determinations in animal feed samples for ruminants through a proficiency test (PT) program. This PT program is organized by Embrapa Cattle Southeast to evaluate laboratories that analyze animal feed samples. Considering the fractions of satisfactory z-scores (%) of evaluated analytes to determine the laboratories performance, the general performance indicator obtained by IPEN - CNEN/SP ranged from 90 to 95% of the satisfactory results during the period of participation in the evaluation, four years.